Cyclization–endoperoxidation cascade reactions of dienes mediated by a pyrylium photoredox catalyst - Gesmundo, Nathan J.; Nicewicz, David A. (Beilstein Journal of Organic Chemistry, 2014)
Triarylpyrylium salts were employed as single electron photooxidants to catalyze a cyclization–endoperoxidation cascade of dienes. The transformation is presumed to proceed via the intermediacy of diene cation radicals. The nature of the diene component was investigated in this context to determine the structural requirements necessary for successful reactivity. Several unique endoperoxide structures were synthesized in yields up to 79%.
Keywords: alkene; cascade; endoperoxide; oxidation; photoredox catalysis